1993
DOI: 10.1111/j.1532-5415.1993.tb07457.x
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Nocturnal Arterial Oxygen Desaturation and Silent Myocardial Ischemia in Patients Presenting for Vascular Surgery

Abstract: Repetitive nocturnal cyclic arterial desaturation and cyclic increases in heart rate are associated with nocturnal myocardial ischemia in individuals with clinical risk factors for ischemic heart disease. Further investigation in a large patient sample utilizing non-invasive monitoring of saturation, heart rate, and blood pressure may provide definitive evidence regarding causation of some of the nocturnal myocardial ischemia occurring in older individuals with vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…4,51 Cardiac complications are the leading cause of postoperative deaths, 7 and several postoperative factors (e.g., hypotension, tachycardia, bleeding, hypoxemia, and pain) are associated with such complications. 16,42,[52][53][54][55][56] Pr eoper ati v e Pr edic tion of C a r di ac Complic ations…”
mentioning
confidence: 99%
“…4,51 Cardiac complications are the leading cause of postoperative deaths, 7 and several postoperative factors (e.g., hypotension, tachycardia, bleeding, hypoxemia, and pain) are associated with such complications. 16,42,[52][53][54][55][56] Pr eoper ati v e Pr edic tion of C a r di ac Complic ations…”
mentioning
confidence: 99%
“…In addition, sleep studies performed on the first postoperative night have shown that sleep is highly fragmented and thus this may also play a role in worsening underlying sleep apnea [34][35][36]. Interestingly, sleep deprivation for 36 hours in patients with mild sleep apnea will worsen oxygenation during sleep [37]. Complications related to OSA seen later in the postoperative course may be due to other factors, however, with increased REM sleep during recovery likely playing a major role.…”
Section: Osa and Perioperative Riskmentioning
confidence: 92%
“…The absence of REM sleep on these nights creates a "REM pressure" that is alleviated by increased density and the increased duration of REM sleep postoperatively on subsequent nights. During REM rebound sleep, REMassociated hypoxemic episodes can increase by three fold on the second and third nights compared with the night before surgery [35,37]. As apneas lengthen and are associated with worsened hypoxia during REM sleep [29], this increase in duration of REM sleep could contribute to aggravation of underlying OSA and nocturnal hypoxia.…”
Section: Osa and Perioperative Riskmentioning
confidence: 98%
“…While suppression of specific sleep stages may occur during administration of these medications, a rebound increase in REM or SWS can occur upon drug withdrawal. A rebound increase in REM sleep can be associated with exacerbation of sleep disordered breathing, along with autonomic instability, potentially leading to adverse hemodynamic effects, myocardial ischemia, and altered mentation [41].…”
Section: Effects Of Medications On Sleep In the Icumentioning
confidence: 99%